STRENGTHENING HR MANAGEMENT AND ACCELERATION OF SALES DIGITAL BASED ON TEMBUNG BERSATU MSMEs DELI SERDANG - Nur Aisyah; Dahrul Siregar; Amrin Mulia U Nst (International Journal of Engagement and Empowerment, 2022)
This study provides an overview of strengthening human resource management and accelerating digital-based sales at the Tembung Bersatu Deli Serdang SMEs. Reinforcement provides self-motivation in the belief in the ability of self-potential in improving the household economy and in efforts to accelerate sales that are increasingly rampant towards IT. Sales of digital-based products, so that they can follow digital developments that have an influence, must hold promotions and deals based on digital. MSME business actors will provide sales to consumers, such as those by MSMEs in Tembung Bersatu Deli Serdang